Renouveler la macroéconomie postkeynésienne ? Les modèles stock-flux cohérent et multi-agents - Mickaël Clévenot; Edwin Le Héron (Revue de la Régulation)
The 16th issue of the Regulation review renews the opportunity of an exchange on the post Keynesian current approach (cf. n°10), especially on post Keynesian macroeconomic modeling. There are five works on this topics among which four use the stock-flow consistent approach of Wynne Godley and Marc Lavoie and fifth relies on multi-agents modeling (ABM). Finally, several reading notes are introduced at the end of the review issue, to describe the latest book of Marc Lavoie entitled Post-Keynesian Economics, which presents new foundations of this current of thoughts.